2007
DOI: 10.1291/hypres.30.285
|View full text |Cite
|
Sign up to set email alerts
|

Specific Serotonin Reuptake Inhibition in Major Depressive Disorder Adversely Affects Novel Markers of Cardiac Risk

Abstract: There exists a growing body of evidence linking depression with cardiovascular events, although the mechanisms responsible remain unknown. We investigated the role of the autonomic nervous system and inflammation in the link between coronary heart disease and major depressive disorder (MDD), and examined the cardiac risk modification following pharmacological treatment of depression. We measured cardiac baroreflex function, heart rate variability, pulse pressure and high sensitivity C-reactive protein (hsCRP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 46 publications
(60 reference statements)
2
53
0
3
Order By: Relevance
“…We have previously documented a reduction in vagal activity, as indicated by a diminution in heart rate variability and baroreflex sensitivity, in patients with depression after serotonin-specific reuptake inhibitor therapy. 2 Moreover, Licht et al, 3 in an earlier analysis of data from the Netherlands Study of Depression and Anxiety, documented a reduction in heart rate variability in patients with depression. The association between diminished heart rate variability and depression was driven largely by the use and dose of antidepressants.…”
Section: To the Editormentioning
confidence: 97%
“…We have previously documented a reduction in vagal activity, as indicated by a diminution in heart rate variability and baroreflex sensitivity, in patients with depression after serotonin-specific reuptake inhibitor therapy. 2 Moreover, Licht et al, 3 in an earlier analysis of data from the Netherlands Study of Depression and Anxiety, documented a reduction in heart rate variability in patients with depression. The association between diminished heart rate variability and depression was driven largely by the use and dose of antidepressants.…”
Section: To the Editormentioning
confidence: 97%
“…In total, 140 case-control and 30 treatment 76,83,93,110,116,129,138,141,155,175,[187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] studies were eligible for inclusion in the quantitative synthesis (151 case-control and 43 effect sizes for analysis); 10 of the studies were included in both the case-control and treatment analyses. 76,83,93,110,116,129,138,141,155,175 Four subgroups of disorders (mood, anxiety-related, psychotic and substance dependence disorders) and 2 classes of psychotropic medications (antidepressants and antipsychotics) were included. Table 1 reports study characteristics for case-control and treatment studies, separated by diagnostic group or type of psychotropic medication, respectively (see Appendix 1, Tables S1 and S2, for individual study characteristics).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Bär et al 189 Davidson et al 190 188 Dawood et al 110 Khaykin et al 191 Koschke et al 116 Lederbogen et al 192 Prasko et al 76 Rechlin 194 Rechlin 194 Rechlin et al 196 Tucker et al 83 Udupa et al 197 Udupa et al 198 Yeragani et al 201 189 Khaykin et al 191 Lederbogen et al 192 McLeod et al 193 Rechlin 194 Rechlin et al 195 Rechlin et al 195 Rechlin et al 196 Tulen et al 129 Udupa et al 198 Yeragani et al 199 Yeragani et al 200 …”
Section: Bär Et Almentioning
confidence: 99%
“…A single study reported opposite findings (Dawood et al 2007). A meta-analysis reported a marginally significant decrease in CRP after anti-depressant treatment (Hiles et al 2012), while higher CRP levels at baseline were found to predict the persistence of depressive symptoms over 5 years (Zalli et al 2015).…”
Section: Peripheral Biomarkersmentioning
confidence: 99%